Heteroatom-substituted tetra(3, 4-pyrido)porphyrazines: a stride toward near-infrared-absorbing macrocycles. Issue 20 (17th April 2015) - Vachova, Lenka; Machacek, Miloslav; Kučera, Radim; Demuth, Jiri; Cermak, Pavel; Kopecky, Kamil; Miletin, Miroslav; Jedlickova, Adela; Simunek, Tomas; Novakova, Veronika; Zimcik, Petr
Abstract : Synthesis and photophysical properties are reported for substituted tetra(3, 4-pyrido)porphyrazines that absorb light as far as at 800 nm. Abstract : A synthesis procedure for heteroatom-substituted tetra(3, 4-pyrido)porphyrazines that absorb light near 800 nm was developed. Based on the observed relationships between the structure and photophysical parameters, a novel highly photodynamically active (IC50 = 0.26 μM) compound was synthesized and biologically characterized.